Human Enterovirus in the Gastrocnemius of Patients With Peripheral Arterial Disease. Issue 4 (6th August 2013) - Kim, Julian K. S.; Zhu, Zhen; Casale, George; Koutakis, Panagiotis; McComb, Rodney D.; Swanson, Stanley; Thompson, Jonathan; Miserlis, Dimitrios; Johanning, Jason M.; Haynatzki, Gleb; Pipinos, Iraklis I.
Abstract : Background: Peripheral arterial disease (PAD) is characterized by myofiber degeneration and loss of function in muscles of the lower limbs. Human enterovirus (HEV) infection has been implicated in the pathogenesis of a number of muscle diseases. However, its association with PAD has not been studied. In this study, we tested the hypothesis that infectious HEV is present in skeletal muscle of patients with PAD and is associated with severity of disease. Methods and Results: Gastrocnemius biopsies from 37 patients with PAD and 14 controls were examined for the presence of HEV RNA, viral capsid protein, viral RNA copy number, and viral infectivity. HEV RNA was detected in 54% of the biopsies from patients with PAD but was not detected in muscle biopsies from control patients. This difference in prevalence among PAD and control patients was significant at P <0.001. Viral RNA copy numbers were increased significantly at the later stages of disease; Fontaine Stage IV (10 5.50 copies/mg muscle wet weight, at P <0.005) and Stage III (10 4.87 copies/mg, at P <0.010) compared to Stage II (10 2.50 copies/mg). Viral replication was confirmed by the presence of the negative‐strand of viral RNA in all specimens positive for HEV RNA. Cultures of HeLa and human skeletal muscle cells treated with muscle homogenates showed HEV replication and the presence of HEV capsid protein. Conclusion: Our data identified infectious HEV in the gastrocnemius of PAD patients but not in controls. Viral copy number and prevalence of infection were higher in the later stages of disease. Our data point to the need for further studies to determine the contribution of HEV infection to the pathophysiology of PAD.